"Diaries" by Oles Gonchar of 1984 - 1995: in dialogue with eternity - Гажа, Тетяна Павлівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article focuses on the diary entries of Oles Honchar, one of the prominent writers of the second half of the twentieth century, an active cultural and public figure. Records written in the last decade of the writer’s life (1984 - 1995). The article covers philosophical reflections on the world, Ukraine, its past, future, Ukrainian language and spirituality. The views of the author are confirmed by a number of quotations. The philosophical content of O. Honchar’s reflections correlates with the existential outlook (the death of loved ones causes him a set of emotions, thoughts, feelings). In many diary entries, loneliness is felt. In the system of vital values of O. Gonchar, the writer and man - faith in Ukraine, love for Ukraine. The world of Oles Gonchar in diaries is filled with landscape paintings that reveal his understanding of the homeland, the meaning of life. The article notes that the powerful words of O. Honchar testify to the experience of a person, who analyzes the events of past years, commented; the author of the diary is in dialogue with the descendants, gives answers to questions. Attitude to nature O. Gonchar is considered as the most important factor in shaping the views on the world, spirituality and internal wealth of man. From the entries of O. Gonchar’s diary, the author appears not to be an indifferent observer. His reflections on reading, seeing, meeting with extraordinary personalities, forced to reflect on life, sometimes, eternity. Entries in the diary of Oles Gonchar are the attitude and thinking of a Ukrainian who always remains. "... how much tragedy in my life, how little I had to experience light days! Is that childhood with its magnanimity and kindness of people of such rare as Grandma?.